Alterations of gut microbiota during the development of a hyperuricemia rat model - Cunlong Lu; Long Li; Tuo Shi; Yu Li; Yanbing Zhou (Medicine in Microecology)
Hyperuricemia has been demonstrated to be correlated with gout and other metabolic disorders, and like the obesity and diabetes, it may be associated with gut microbial dysbiosis. However, recently, research on the changes of serum uric acid and gut microbiota during the development of hyperuricemia was sparse. The main objective of this study is to explore the changes of serum uric acid and gut microbiota in a hyperuricemia rat model. 16S rDNA obtained from fecal samples of rats were sequenced to characterize the diversity and composition of microbial communities. Unweighted UniFrac-based principal coordinate analysis (PCoA) of 16S rDNA sequences showed separated clusters between the model group and the control group. Our findings showed that the model group showed a decreased abundance of Lactobacillus, and the butyrate-producing bacteria Ruminococcus spp. and Roseburia spp., while an increased abundance of opportunistic pathogens, including Proteobacteria, Bacteroides fragilis, and Escherichia coli during the establishment of the hyperuricemia rat model. In addition, purine and uric acid metabolism of gut microbiota in the model group was improved. In conclusion, our results demonstrated that the diversity, composition and function of gut microbiota in the hyperuricemia rat model significantly altered.